Italian Real-World Analysis of the Impact of Polypharmacy and Aging on the Risk of Multiple Drug–Drug Interactions (DDIs) in HCV Patients Treated with Pangenotypic Direct-Acting Antivirals (pDAA) - Fagiuoli S; Toniutto P; Coppola N; Ancona DD; Andretta M; Bartolini F; Ferrante F; Lupi A; Palcic S; Rizzi FV; Re D; Alvarez Nieto G; et al. (Dove Medical Press, 2023)
Stefano Fagiuoli,1 Pierluigi Toniutto,2 Nicola Coppola,3 Domenica Daniela Ancona,4 Margherita Andretta,5 Fausto Bartolini,6 Fulvio Ferrante,7 Alessandro Lupi,8 Stefano Palcic,9 Francesca Vittoria Rizzi,10 Davide Re,11 Gema Alvarez Nieto,12 Candido Hernandez,13 Francesca Frigerio,14 Valentina Perrone,14 Luca Degli Esposti,14 Alessandra Mangia15 1Department of Medicine and Surgery, University of Milan Bicocca & Gastroenterology Hepatology and Transplantation Unit, ASST Papa Giovanni XXIII, Bergamo, Italy; 2Hepatology and Liver Transplantation Unit, Azienda Ospedaliero Universitaria, Udine, Italy; 3Infectious Diseases Unit, University of Campania L. Vanvitelli, Naples, Italy; 4Dipartimento Farmaceutico ASL BAT, Trani, Italy; 5UOC Assistenza Farmaceutica Territoriale, Azienda Ulss 8 Berica, Vicenza, Italy; 6Dipartimento Farmaceutico-Usl Umbria 2, Terni, Italy; 7Dipartimento Diagnostica Ed Assistenza Farmaceutica - ASL Frosinone, Frosinone, Italy; 8Struttura Complessa Di Cardiologia - ASL VCO, Omegna, Italy; 9Farmaceutica Territoriale- Azienda Sanitaria Universitaria Integrata Giuliano-Isontina (ASUGI), Trieste, Italy; 10UOS Farmacovigilanza e Monitoraggio Spesa Farmaceutica- ASL BAT, Trani, Italy; 11Servizio Farmaceutico Territoriale ASL Teramo, Teramo, Italy; 12Gilead Sciences, Medical Affairs Italy, Milan, Italy; 13Gilead Sciences, Global Medical Affairs, London, UK; 14Clicon S.r.l., Health Economics and Outcomes Research, Bologna, Italy; 15Gastroenterology and Transplant Hepatology, Papa Giovanni XXIII Hospital, Bergamo, 24127, ItalyCorrespondence: Luca Degli Esposti, CliCon S.r.l. Società Benefit, Health, Economics & Outcomes Research, Via Murri, 9, Bologna, 40137, Italy, Tel +390544 38393, Email luca.degliesposti@clicon.itPurpose: The study aims at investigating the impact of polymedication and aging in the prevalence of multiple drug-drug interactions (DDIs) on HCV patients treated with sofosbuvir/velpatasvir (SOF/VEL) or glecaprevir/pibrentasvir (GLE/PIB).Patients and Methods: This is a retrospective analysis based on administrative data covering around 6.9 million individuals. Patients treated with SOF/VEL or GLE/PIB over November 2017-March 2020 were included. Index date corresponded to SOF/VEL or GLE/PIB first prescription during such period; patients were followed up for treatment duration. Analyses were then focused on patients with ≥ 2 comedications at risk of multiple DDIs. The severity and the effect of multiple DDI were identified using the Liverpool University tool.Results: A total of 2057 patients with SOF/VEL and 2128 with GLE/PIB were selected. Mean age of SOF/VEL patients was 58.5 years, higher than GLE/PIB ones (52.5 years) (p < 0.001), and patients > 50 years were more present in SOF/VEL vs GLE/PIB cohorts: 72% vs 58%, (p < 0.001). Most prescribed co-medications were cardiovascular, alimentary and nervous system drugs. Proportion of patients with ≥ 2 comedications was higher in SOF/VEL compared to GLE/PIB cohort (56.5% vs 32.3%, p < 0.001). Those at high-risk of multiple DDIs accounted for 11.6% (N = 135) of SOF/VEL and 19.6% (N = 135) of GLE/PIB (p < 0.001) patients with ≥ 2 comedications. Among them, the potential effect of DDI was a decrease of DAA serum levels (11% of SOF/VEL and GLE/PIB patients) and an increased concentration of comedication serum levels (14% of SOF/VEL and 42% of GLE/PIB patients).Conclusion: This real-world analysis provided a thorough characterization on the burden of polymedication regimens in HCV patients treated with SOF/VEL or GLE/PIB that expose such patients to an increased risk of DDIs. In our sample population, SOF/VEL regimen was more frequently detected on elderly patients and on those with ≥ 2 comedications at risk of multi-DDI, ie, among patients characterized by higher rates of comorbidities and polypharmacy.Keywords: administrative database, glecaprevir/pibrentasvir, hepatitis C, sofosbuvir/velpatasvir, polymedication